Anti-hyperglycemic and Immunomodulatory Activity of a Polyherbal Composed of Sesbania grandiflora, Salacca zalacca and Acalypha indica - Zamroni, Ahmad; Zubaidah, Elok; Rifa'i, Muhaimin; Widjanarko, Simon Bambang (Graduate School, Universitas Brawijaya, 2018)
Diabetes has become a serious global public health problem due to its high prevalence and mortality. Unfortunately, current anti-diabetic drugs are having some limitations and adverse effects. Therefore, searching for a new anti-diabetic agent is an urgent challenge. In this research, we examined the effectiveness of a traditional anti-diabetic polyherbal composed of Sesbania grandiflora seeds, Salacca zalacca leaves and Acalypha indica roots (2:1:1). The study was aimed to explore the anti-hyperglycemic effect of the polyherbal in STZ-induced diabetic mice and to investigate the immunomodulatory activity involved in the process of controlling hyperglycemia. Our results showed that the polyherbal water extract (150 mg.kgBW-1) could suppress blood glucose elevation and preserve pancreatic islet of diabetic mice. Moreover, the polyherbal treatment could normalize the relative amount of activated CD4+CD62L- and CD8+CD62L- T cells. The polyherbal extract also stimulated the production of CD4+CD25+FoxP3+ regulatory T cells (Tregs) which is known to play an important role in diabetes control. In addition, polyherbal treatment also increased the relative amount of anti-inflammatory cytokines IL-10 and TGF-β. These results revealed that the polyherbal extract has an anti-hyperglycemic and immunomodulatory activity that may provide beneficial function in diabetes healing. Keywords: Antidiabetes, Immunomodulator, Polyherbal, Regulatory T cell.